A journey through the lectin pathway of complement—MBL and beyond. Issue 1 (November 2016) - Garred, Peter; Genster, Ninette; Pilely, Katrine; Bayarri‐Olmos, Rafael; Rosbjerg, Anne; Ma, Ying Jie; Skjoedt, Mikkel‐Ole
Summary: Mannose‐binding lectin (MBL), collectin‐10, collectin‐11, and the ficolins (ficolin‐1, ficolin‐2, and ficolin‐3) are soluble pattern recognition molecules in the lectin complement pathway. These proteins act as mediators of host defense and participate in maintenance of tissue homeostasis. They bind to conserved pathogen‐specific structures and altered self‐antigens and form complexes with the pentraxins to modulate innate immune functions. All molecules exhibit distinct expression in different tissue compartments, but all are found to a varying degree in the circulation. A common feature of these molecules is their ability to interact with a set of serine proteases named MASPs (MASP‐1, MASP‐2, and MASP‐3). MASP‐1 and ‐2 trigger the activation of the lectin pathway and MASP‐3 may be involved in the activation of the alternative pathway of complement. Furthermore, MASPs mediate processes related to coagulation, bradykinin release, and endothelial and platelet activation. Variant alleles affecting expression and structure of the proteins have been associated with a variety of infectious and non‐infectious diseases, most commonly as disease modifiers. Notably, the severe 3MC (Malpuech, Michels, Mingarelli, and Carnevale) embryonic development syndrome originates from rare mutations affecting either collectin‐11 or MASP‐3, indicating a broader functionality of the complement system than previously anticipated. This review summarizes the characteristics of the molecules in the lectin pathway.